Napkin finance : build your wealth in 30 seconds or less - Hay, Tina (Dey Street an imprint of William Morrow, 2019)
"Surveys have found that two thirds of Americans can't pass a basic financial literacy test, and nine in ten believe personal finance should become a required high school course. Tina Hay understands the confusion. While attending Harvard Business School, she struggled to keep up with classmates-many of whom came from the banking world-when it came to understanding jargon and numbers-heavy concepts. Tina developed a visual learning strategy using sketches and infographics that helped her succeed in her studies and master even the most complex financial topics. Since then, Tina founded Napkin Finance, a thriving company built on the concept of taking seemingly overwhelming topics--such as budgeting, investments, and retirement accounts--and turning them into simple, skimmable explanations. Now, she's synthesized the most important content into this personal finance handbook. Napkin Finance includes dozens of individual learning modules, on topics ranging from credit scores to paying off student loans to economics and blockchain."--Amazon.